Exploring the experience of Nigerian women in technical and vocational education in polytechnic institutions - Akor, Robert Thomas (2015)
Nigerian government is making frantic efforts to drive her economy by laying emphasis on technical and vocational education to enable her compete favorably in the global market. Emphasis of government is in Polytechnic education where skills for self-reliant and economic growth are a priority. However, women are not embracing this opportunity by participating in technical and vocational education that will equip them with skills and contribute to national development. Opportunities need to be explored as to ensure their participation in nation building. Therefore, the aim of this study was to explore the experience of Nigerian women in technical and vocational education in Polytechnic institutions. The in-depth information about the phenomenon formed the basis to improve the access and participation of women in this field. Specifically the research question includes (1) How do Nigerian women portray their position in technical and vocational education? (2) What are the reasons given by Nigerian women for the under representation of women in technical and vocational education in Polytechnic Institution? (3) How do the Nigerian women strategize themselves to remain viable in technical and vocational education environment? (4) How do Nigerian women foresee the action to be taken to resolve underrepresentation in technical and vocational education in Polytechnic Institution? The qualitative research design which employed the use of phenomenological methodology was used in conducting this study. The participants comprised female students enrolled in technical and vocational education in Polytechnic Idah. In all 14 prospective participants were selected from the Polytechnic using purposive sampling technique. The primary data collection technique that was adopted for this study was interview. Observations, review of documents and field notes were employed to supplement the data collected. The data collected were analyzed according to categories and themes and the findings and discussions were presented according to each research question. Triangulation, peer review and member checks were used to validate the findings. Going by the research questions several information and findings include stereotyping,intimidation, sexual harassment, culture, among others as women’s experience in technical and vocational education in Polytechnic. For Nigeria to attain her technological fit the challenges confronting women in technical and vocational education must be recognized and fought vigorously. Unless women have increased access to technical and vocational education in order to build diverse technical and vocational skills their vulnerability to unemployment and poverty will be on the rise. There is need for comprehensive reform toward technical and vocational education and a deliberate attempt to lift the status of women in this program the only panacea to technological ender ado in Nigeria. Technical and vocational education can serve an unprecedented role of breaking the economic divides that generate imbalances in the lives of men and women. The findings of this study will guide government and other agencies responsible for education to develop a framework for improving the access and participation of women in technical and vocational education.